Semiotic Analysis of Overthinking in Music Vidio Takut by Idgitaf - Br. Perangin-angin, Alemina; Syahputra, Fikry Prastya; Andayani, Widya; Jalil, Zurriyati A. (Talenta Publisher, 2023)
Overthinking is one of the big problems for young people nowadays. The release of the music video of Takut by Idgitaf is very relatable to the overthinking phenomenon that occurs in young people. This research aims to analyze overthinking representations in the music video of Takut by Idgitaf.Â The method used in this analysis is qualitative and the theory of Roland Barthes to identify myth, denotation, and connotation meanings in the video. Semiotic signs are found in the music video Takut by Idgitaf, both visually through video and verbally through the lyrics. The research proves that the music video for this song of Takut by Idgitaf has been signed visually and verbally, describing a person's overthinking attitude towards everything, especially young people. This song explores the feelings of young people nowadays about the stress of thinking about the future, the fear of failure, and the anxiety about getting older also means increased responsibility. Besides, this song conveys how young people can deal with overthinking. Â